Germinação, desenvolvimento inicial e concentração de pigmentos em mudas de physalis (Physalis spp.) produzidas em diferentes ambientes - Mezzalira, Éder Júnior (2013)
The use of different environments can be a limiting factor for the development of seedlings of species of Cape gooseberry. Given the above, the objective of the present study to evaluate the initial development of species of physalis, subjected to different environments. The experimental design was randomized blocks, in 3 x 3 factorial schemes, containing four repetitions. The experiment conducted in the period from February to May 2012 in Horticultural and Biological Control Station "Professor Mário César Lopes", belonging to Unioeste, Campus, in Marechal Cândido Rondon-PR. Treatments were composed of three species of Cape gooseberry (Physalis peruviana, p. angulata and p. pubescens) x three environments (greenhouse/EST-colorless plastic coated 150 microns; sombrite/SBT-75% of the light permeability and full sun/PLS-local fully open), being monitored the emergency speed index of seedlings in 30 days. To 76 days after sowing evaluated the leaf area, dry weight of leaves, stems, and roots and counting the number of leaves, plant height and stem diameter. For the determination of biochemical levels of chlorophyll a and b, anthocyanin, carotenoids polifenoloxidase, peroxidase and proteins. Collected into plant tissue of leaves, before sunrise, between the 05:00 and 6:30 hs, having been put up in aluminum foil, properly identified the treatments, which is stored in the container with ice and then frozen. The environment sombrite provides highest rate for the species of Physalis angulata, p. peruviana and p. pubescens. The environments and sombrite were very similar in initial development to Physalis angulata, p. peruviana and p. pubescens and may be used for the production of seedlings of these species. The Physalis peruviana has the largest average levels of all photosynthetic pigments, compared to p. angulata. The Physalis peruviana has been greater than p. pubescens, in relation to carotenoids. The average levels of total protein of p. angulata overcame the other species. In General, species of physalis plants kept in the EST and SBT, outweigh the environment PLS